2016
DOI: 10.1165/rcmb.2015-0218tr
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea Research in Animals. Past, Present, and Future

Abstract: Obstructive sleep apnea (OSA) is a common disorder that describes recurrent collapse of the upper airway during sleep. Animal models have been pivotal to the understanding of OSA pathogenesis, consequences, and treatment. In this review, we highlight the history of OSA research in animals and include the discovery of animals with spontaneous OSA, the induction of OSA in animals, and the emulation of OSA using exposures to intermittent hypoxia and sleep fragmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 69 publications
1
68
0
1
Order By: Relevance
“…As recently reviewed,(18) very few mammals develop OSA spontaneously, and the OSA tends to be relatively mild. Therefore, most experimental models simulate OSA by exposing animals to deconstructed features of OSA such as either intermittent hypoxia (IH) or sleep fragmentation (SF) alone.…”
Section: Experimental Models Of Osa and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…As recently reviewed,(18) very few mammals develop OSA spontaneously, and the OSA tends to be relatively mild. Therefore, most experimental models simulate OSA by exposing animals to deconstructed features of OSA such as either intermittent hypoxia (IH) or sleep fragmentation (SF) alone.…”
Section: Experimental Models Of Osa and Cancermentioning
confidence: 99%
“…(26) How well IH models recapitulate human disease has been questioned due to the severity of the hypoxia induced as well as the lack of other features of OSA. (18) Going forward, it will be important to develop more clinically relevant IH models to understand better the OSA-cancer link. Additionally, animal experiments to date have been limited to only two types of cancer (melanoma and lung) and the effect of IH on distant metastasis has not been elucidated.…”
Section: Experimental Models Of Osa and Cancermentioning
confidence: 99%
“…The disorder is characterized by exposure to recurrent cyclical bouts of hypoxia and re-oxygenation, due to repeated obstructions of the upper airway that interrupt pulmonary airflow: OSAS is an oxidative stress disorder (Lavie, 2003). Notwithstanding the multifactorial nature of the complex respiratory condition, there is a general consensus within the field that exposure to chronic intermittent hypoxia, typifying OSAS, is injurious to many tissues (Jun et al 2008;Chopra et al, 2016;O'Halloran, 2016). Indeed, animal models of CIH recapitulate many of the morbidities reported in OSAS patients, thereby serving as a useful model of the disease (Chopra et al, 2016;O'Halloran, 2016).…”
Section: Chronic Intermittent Hypoxia Is a Dominant Feature Of Osas Dmentioning
confidence: 99%
“…Notwithstanding the multifactorial nature of the complex respiratory condition, there is a general consensus within the field that exposure to chronic intermittent hypoxia, typifying OSAS, is injurious to many tissues (Jun et al 2008;Chopra et al, 2016;O'Halloran, 2016). Indeed, animal models of CIH recapitulate many of the morbidities reported in OSAS patients, thereby serving as a useful model of the disease (Chopra et al, 2016;O'Halloran, 2016). There is strong evidence that CIH alters cardiorespiratory control, through adverse actions at multiple sites in the integrative control network (Peng et al, 2003(Peng et al, , 2006(Peng et al, , 2014Rey et al, 2004;Julien et al, 2008;Del Rio et al, 2010;Moraes et al, 2013;Zanella et al, 2014;Garcia et al, 2016), disrupting the rhythm and pattern Zanella et al, 2014;Garcia et al, 2016) of central respiratory drive, with evidence of increased propensity for central apnoea following CIH exposure Donovan et al, 2014;Souza et al, 2015) Fibre type transitions have been described in some studies (Pae et al, 2005;Liu et al, 2009), but it appears that upper airway muscle dysfunction is not dependent on fibre-type remodelling or atrophy (Skelly et al, 2012a), phenotypic differences that are perhaps dependent on the experimental paradigm employed in the studies, which varies considerably in terms of pattern, duration and intensity of hypoxic exposure.…”
Section: Chronic Intermittent Hypoxia Is a Dominant Feature Of Osas Dmentioning
confidence: 99%
“…This observation has led to the concept that IH plays a key role in the genesis of cardiovascular disease triggered by OSA and opened the possibility to study the intermediate mechanisms linking OSA to cardiovascular disease. 8,9 It is surprising, however, that researchers have paid little attention to exploring the reversibility of the cardiovascular and metabolic effects induced by OSA. One previous study found that the impaired glucose homeostasis induced by IH was partially improved with cessation of exposure to IH.…”
mentioning
confidence: 99%